Body surface measurements of polish sprinters - Kobielski, Bernard (Anthropological Review, 1974)
The author have analysed data concerning body surface measurements of 90 the best Polish sprinters. For comparison are also taken measurements of 19 sprinters from Bulgaria, Romania and Germany. Results are presented in table 1.